Comparative evaluation of enamel surface roughness after minimally invasive treatment of white spot lesions: An in vitro study / I'udzuri Md Jazam - I'udzuri, Md Jazam (2021)
Objective: To investigate the surface roughness of resin infiltrated proximal white spot lesions (WSLs) with ICON® subjected to a pH cycling challenge and compare its surface roughness with WSLs treated with that of Duraphat®. Materials and Methods: Sixty extracted sound premolars were used in this in vitro study. Optical coherence tomography (OCT) was used for baseline enamel readings and randomly divided into four groups having fifteen specimens in each. Groups were assigned as: Sound (negative control), Demineralised (positive control), ICON®, and Duraphat®. All specimens except for the Sound group were subjected to an initial demineralisation in a solution containing 2.2mM calcium chloride, 2.2mM potassium meta-phosphate, and 50mM acetate buffer at a pH of 4.5 for 7 days and enamel changes were confirmed using OCT. The Sound and Demineralised groups acted as control while the other two groups were applied resin infiltration (ICON®) and fluoride varnish (Duraphat®). All the specimens were measured using a non-contact profilometer (3D Alicona) for baseline surface roughness (Ra) prior to being subjected to a pH cycling regime for 7 days. Ra analysis was after pH cycling was conducted and mean differences recorded. Results: Data were analysed with oneway analysis of variance (ANOVA), and repeated measure ANOVA using SPSS (ver. 23) at a=0.05. The Ra at baseline revealed significant differences across the group except for the comparison of ICON® (0.314μm±0.004) to sound enamel (0.313μm±0.028). After pH cycling the enamel surfaces treated with ICON® (0.422μm±0.004) were significantly smoother than those treated with Duraphat® (0.583μm±0.003). After 7 days of acidic challenge, ICON® exhibited the least change in Ra value (0.108μm). Conclusions: Within the limitations of the study, the results showed that WSLs treated with ICON® showed approximately the same surface roughness as sound enamel, suggesting suitability for the treatment of WSL.